Improvement of Perceived Value of Apartment: Strategic Analysis Using IPA, SWOT, and AHP - Ismail, Akhmad; Nathanael Andika, Ignatius; Rahman, Rahman; Babolian Hendijani, Roozbeh (Interdisciplinary Social Studies, 2023)
Background: After the covid 19 pandemic subsided, the world was faced with a global recession. The property industry experiences a downturn, especially in countries that are severely affected by the recession. However, the property business, in particular, apartments must continue to run and require a strategy to overcome this. Aim: The purpose of this study was to develop a strategy to increase perceived value using three methods of IPA, SWOT, and AHP. Method: The quantitative method uses 130 customer respondents. 30 for the reliability validity test and 100 for the main test on perceived value variables (functional, social, and emotional). Findings: The results of the IPA in quadrant A form the basis for making IFE and EFE strategies. IFE and EFE strategies are weighted to determine IFE and EFE matrices. Furthermore, a SWOT  matrix was carried out to formulate concrete strategies based on SO, WO, ST, and WT. Strategies will be ranked using AHP. The strategy includes renovating the roof and repainting the facade of the building, using higher quality and durable building materials, holding service training for tenant relations and optimizing cleaning team SOPs, making agreements with buyers regarding rules for repairing damage/leaks, promoting green and clean movements for owners or occupants, expanding the customer segment market, contacting unit owners to be managed by rental management developers, opening multiple payment platforms with marketplaces, continuing to do marketing to target customers, cooperating with sales agents and other external parties, and rescheduling those with payment difficulties.